2020
DOI: 10.1155/2020/1320278
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mechanism on the Medullary Visceral Zone Inhibiting the Cholinergic Anti-inflammatory Pathway Induced by Sepsis

Abstract: Inflammatory storm is an important pathological mechanism of multiple organ dysfunction, and it is associated with most deaths in septic patients, deserving to be studied. Recent findings have confirmed that the Medullary Visceral Zone (MVZ) regulates inflammation and immunity through the cholinergic anti-inflammatory pathway (CAP), but how sepsis affects the MVZ and leads to uncontrolled inflammation remain unclear. The current study reported that sepsis induced MVZ to inhibit CAP which underlies the inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…After 3 days, rats were euthanized under anesthesia with inhalation of isoflurane [ 17 ] to collect the medulla oblongata for reverse transcription-polymerase chain reaction (RT-PCR), TdT mediated dUTP nick end labeling (TUNEL), and Fluorescent immunolabeling analysis. Though these results have been reported in our previous study [ 12 ], it is necessary to remind it again.…”
Section: Methodssupporting
confidence: 57%
See 2 more Smart Citations
“…After 3 days, rats were euthanized under anesthesia with inhalation of isoflurane [ 17 ] to collect the medulla oblongata for reverse transcription-polymerase chain reaction (RT-PCR), TdT mediated dUTP nick end labeling (TUNEL), and Fluorescent immunolabeling analysis. Though these results have been reported in our previous study [ 12 ], it is necessary to remind it again.…”
Section: Methodssupporting
confidence: 57%
“…As reported in previous study [ 12 , 17 ], after 7 days of adaptive feeding the formal experiment begins, 3 days after the relevant intervention, the rats’ blood and brain tissue were harvested for detection. The first experiment carry out such analysis as short-term HRV, TdT mediated dUTP Nick End Labeling (TUNEL), Immunofluorescence and Quantitative Reverse Transcription-Polymerase Chain Reaction (RT-PCR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary experiments confirmed that activation of α 7nAChRs significantly improved MVZ neuroinflammation and apoptosis [ 61 , 62 ]: in sepsis, intraperitoneally administered GTS-21, a specific agonist for α 7nAChRs, significantly reduced the apoptosis of the cholinergic and catecholaminergic neurons in MVZ in septic rats, accompanied by the elevated expression of tyrosine hydroxylase (TH) and choline acetyltransferase (CHAT), which significantly reversed the inhibition of CAP and the inflammatory storm, while intraperitoneally administered MLA, a specific antagonist for α 7nAChRs, does the opposite. Therefore, activation of α 7nAChRs not only directly inhibits the overactive systemic inflammation and immunity but also resumes the inflammatory and dysfunctional MVZ, thereby restoring CAP's regulation of inflammation.…”
Section: Primary Regulation: α 7nachrs Mediated the Inflammatory Reflexsupporting
confidence: 62%
“…In MVZ, neuroinflammation has a comprehensive influence on nerves architecture, synaptic plasticity, and nerve function. Studies show that cholinergic and catecholaminergic neurons in MVZ went through significant apoptosis and inactiveness, which contributes to the inhibition of CAP and the acceleration of the inflammatory storm in early sepsis [ 61 , 62 ]. Neuroinflammation facilitates reactive glial cells in the brain, releasing cytokines and damage-associated molecular patterns (DAMPs), which promote cell adhesion, migration, proliferation, and angiogenesis [ 86 ].…”
Section: Neuroinflammation Induced By Sepsis Causes Extensive Damage To the Cap's Regulation On Inflammation And Immunitymentioning
confidence: 99%